Determining optimal MRI follow-up after transsphenoidal surgery for pituitary adenoma: Scan at 24 hours postsurgery provides reliable information - (:unkn) unknown (My University, 2001)
There is no agreed-upon schedule for MRI follow-up after pituitary adenoma removal via the transsphenoidal approach. Our aim was to establish a plan for MRI follow-up after pituitary surgery. Eighty pituitary adenoma cases (25 microadenomas, 30 macroadenomas that did not infiltrate the cavernous sinus, and 25 macroadenomas with cavernous sinus infiltration) were prospectively studied with MRI following tumor resection via the transsphenoidal approach. Each patient was imaged at 24 hours, at 3, 6 and 9 months, and at 1 year or more postsurgery. The parameters studied were residual tumor, synthetic packing material (Gelfoam) versus fat graft, and normal pituitary, hypophyseal stalk and optic chiasma. The size of the pituitary structure as a whole was also measured. The latter was studied quantitatively, and the findings for the rest of the parameters were evaluated qualitatively, based on the examiners' confidence in their assessment. The final MRI study, done at least 1 year postsurgery in all cases, was considered the reference MRI for all scans. MRI performed 24 hours after surgery was diagnostically accurate for residual tumor and valuable for visualizing normal sellar structures. The findings also showed that fat packing takes longer to resorb than Gelfoam, but produces no potentially confounding contrast enhancement. An algorithm based on the results is presented for postsurgical MRI assessment of pituitary adenoma patients in which the scan at 24 hours postsurgery is the major factor that determines the timing of later rechecks.
Keywords: Magnetic resonance imaging; Pituitary adenoma; Transsphenoidal surgery